Karakteristik Fisik dan Kimia Sambal Gurita dengan Pra-Proses Perlakuan Cabai yang Berbeda - Kinanti Fitrah Rahmadhani; Elly Kurniawati (Politeknik Negeri Jember, 2022)
Sambal is one type of complementary food obtained from the main ingredient of chili (Capsicum sp.) which is cooked and processed with the addition of permitted spices or without the addition of other foods. The making of octopus sauce needs a good method or processing method to produce different forms and end results of dishes. This study aims to determine the physical and chemial characteristics of octopus chili sauce and the best treatment with different chili pre-treatment processes. This research was conducted experimentally, with 4 treatments and 3 replications, namely control; Hot Water Blanching; Steam Blanching; Saute. Parameters observed were water activity, water content, pH, and vitamin C. The results showed that saute was chosen as the best treatment with an water activity score of 0.797, water content of 12,98%, pH of 4,76, vitamin C of 32,22%.